Revitalisasi Hutan Pekarangan melalui Budidaya Lada untuk Mendukung Desa Wonoasri sebagai Desa Program Kampung Ilkim - Dewi, Nilasari; Kurnianto, Agung Sih; Bila, Zuyyina Hafsah Salsa (Universitas Mataram, 2023)
Program kampung iklim (Proklim) is an activity that combines climate change mitigation and adaptation efforts at the site level by involving the active participation of the community and various other supporting parties so that the community becomes more resilient to climate change. This service activity aims to develop and reactivate the homestead forest that has been formed by increasing the number and types of plants in the homestead forest so that the Wonoasri Village community is ready to become a Proklim Village. The service was carried out through several activities, namely: program outreach, identification of development locations, pepper cultivation training, monitoring and evaluation. This activity was attended by 12 farmers who were representatives of farmers who were committed to planting pepper in their home forests as a form of implementing community service activities. This. This training received a positive reaction from the people of Wonoasri Village. Lamtoro, gamal, dadap and jaranan wood plants were chosen as plants to be planted in the yard as pepper plants.